Om folkbildningsmässig särart i idrottsrörelsens studieförbund SISU Idrottsutbildarna - Johan Söderman (Dalarna university, 2023)
The position of sports in relation to the Nordic Bildung tradition (e.g. Folkbildning) has historically been contested. Mainly so because sports were associated with competition and elite thinking in ways that contrast popular educational ideals. The purpose of this study is therefore to analyze what distinguishes the contemporary sports movement in terms of Folkbildning in relation to the pedagogical dilemmas and perspectives expressed by actors within the sports movement. The background to the study is a project initiated by the Swedish Sports Confederation (RF) after internal discussions about Folkbildning in their study association SISU Idrottsutbildarna during 2020. Focus group interviews with 4-7 participants were conducted using Zoom and included seven of SISU's 19 local districts (altogether 40 informants). All interviews were around one hour long and were recorded and transcribed. The informants were all active in the study association SISU. The results are presented through the following categories: Folkbildning as an association pedagogy and nursery school, Folkbildning as a pedagogical idea beyond the measurable and Folkbildning as a universal pedagogical method. Overall, the study concludes how perceptions of Folkbildning within the sports movement risks being reduced to a method for solving social problems. At the same time, a unique association pedagogy emerges in the material, permeated with holistic educational ideals and where the sports movement on a more comprehensive and societal level contributes to important educational insights.